Altered interferon-γ expression in lymphocytes as a potential peripheral marker of chronic stress-induced cognitive deficit - Palumbo, María Laura (2018)
It is known that long-term exposure to stressful situations can produce severe consequences affecting behavioral, endocrine and immunological parameters. We have previously shown that stressed BALB/c mice had poor learning performance, which was reverted by glatiramer acetate treatment through a mechanism that likely involved the regulation of the cytokine balance and adult neurogenesis. In addition, recent results suggest that cytokine and neurotrophin expression in the hippocampus displayed similar tendencies as those in the serum. However, if lymphoid cells could be good candidates as peripheral markers of memory impairment have not yet been investigated. For this purpose, we analyzed the spatial memory and the neutrophin and cytokine mRNA levels in lymph nodes and hippocampus in mice submitted to chronic stress treated or not with glatiramer acetate. Results indicated that there was a correlation between the cytokine and neurotrophin mRNA levels in the hippocampus and in the peripheral lymph nodes, and the cognitive performance in BALB/c mice. In particular, our results suggest that altered IFN-γ levels could be used as peripheral biomarker of cognitive deficit and treatment response.